Sweet potato yield and quality as a function of phosphorus fertilization in different soils - Cordeiro, Carlos F. Dos S. [UNESP]; Echer, Fábio R. [UNESP]; Batista, Guilherme D. [UNESP]; Fernandes, Adalton M. [UNESP] (FapUNIFESP (SciELO), 2023)
Phosphorus (P) is an essential nutrient for growth and yield of sweet potatoes; in sandy soils, sweet potato yield and quality may be limited by application of low P doses, mainly in degraded areas. The objective of this work was to evaluate the effect of P doses on yield and quality of sweet potato root tubers grown in tropical sandy soils with different initial P availabilities: 23.2 mg dm-3 (high P-crop rotation) and 3.7 mg dm-3 (low P-post degraded pasture). Two experiments were carried out in a randomized block design, with four replicates. The treatments consisted of P doses (0, 22, 44, 88, and 176 kg ha-1) applied to the planting bed. Tuber yield, number and mean weight of tubers, P concentration in leaves and tubers, exported P, as well as the percentage of starch, reducing sugars, total sugars, and sucrose in the tubers were evaluated. P concentration in the soil was evaluated at the end of the experiment. In the area with high P availability (> 20 mg dm-3-resin), increasing P doses did not increase root tuber yield and decreased root starch concentrations. In the area with low P availability (< 3.7 mg dm-3-resin), root tuber yield and starch concentration peaked when applying 68 and 33 kg ha-1 of P, respectively. In areas after degraded pasture, with low initial soil P concentration, P fertilization for sweet potato crops should be carried out with a P dose of 68 kg ha-1. In areas with crop rotation and adequate soil P concentration, P fertilization should be carried out to replace the amount of P exported by the harvested root tubers to avoid decreases in soil fertility.
Produtividade e qualidade da batata-doce em função da adubação fosfatada em diferentes solos
Keywords: degraded pasture; Ipomoea batatas (L.) Lam; reducing sugars; sandy soil; starch